KONSELING FEMINIS UNTUK MENINGKATKAN PERAN AYAH WARIA (Jurusan Bimbingan dan Konseling Islam, 2016)
This study discuses some factors that affect someone to be a transgender, family interaction and explain the important role as parent using feminist counseling. This study shows that environmentand family interactions are the factors that affect a person becomes transgender. A counselor has several steps to change the role of transgender in parenting use feminist counseling. They are include identification of problem, diagnosis, prognosis and treatment using empowerment techniques which is explain the counselor’s aim and expectations. Understanding of gender’s role explains how to solve trangender’s problem and their role as a parent. It has function to make the client know their research is quite success, some of transgender can change their attitude, their appearance and know their role as a parent